Spirometra (Pseudophyllidea, Diphyllobothriidae) Severely Infecting Wild-Caught Snakes from Food Markets in Guangzhou and Shenzhen, Guangdong, China: Implications for Public Health. (16th January 2014) - Wang, Fumin; Li, Weiye; Hua, Liushuai; Gong, Shiping; Xiao, Jiajie; Hou, Fanghui; Ge, Yan; Yang, Guangda
Abstract : Sparganosis is a zoonotic disease caused by the spargana of Spirometra, and snake is one of the important intermediate hosts of spargana. In some areas of China, snake is regarded as popular delicious food, and such a food habit potentially increases the prevalence of human sparganosis. To understand the prevalence of Spirometra in snakes in food markets, we conducted a study in two representative cities (Guangzhou and Shenzhen), during January–August 2013. A total of 456 snakes of 13 species were examined and 251 individuals of 10 species were infected by Spirometra, accounting for 55.0% of the total samples. The worm burden per infected snake ranged from 1 to 213, and the prevalence in the 13 species was 0 ∼ 96.2%. More than half (58.1%) of the spargana were located in muscular tissue, 25.6% in subcutaneous tissue, and 16.3% in coelomic cavity. The results indicated that Spirometra severely infected snakes in food markets in Guangzhou and Shenzhen, implying that eating snakes has great health risk and improper cooking methods may increase the risk of Spirometra infection in humans in China. Additional steps should be considered by the governments and public health agencies to prevent the risk of snake-associated Spirometra infections in humans.